Produção de chicória da Amazônia cultivada sob densidades de cultivo e poda do pendão floral - Gomes, Rafaelle Fazzi [UNESP]; da Silva, Josiane Pereira [UNESP]; de Gusmão, Sérgio Antonio Lopes; de Souza, Gisele Teixeira (My University, 2013)
Chicory is a vegetable Amazon unconventional flavor that has attracted the attention of researchers for its great versatility, which makes it a promising vegetable. However, jobs are scarce in the literature on cultivation techniques for the species. This study aimed to evaluate the effect of pruning tassel floral and different spacing, the yield on Amazon chicory. Three different spacings: E1 = 0.15 × 0.15 m, with 44 plants m2, E2 = 0.20 × 0.20 m, with 25 plants m2, and E3 = 0.25 × 0.25 m, with 16 plants m2, with and without pruning floral tassel. The experiment was conducted in a randomized block design in a split plot design 3 × 2, with six replications. The characteristics evaluated were: number of leaves, fresh weight and dry weight of shoots, number of tassel floral tassel floral fresh weight, yield (kg m-2), and leaf area index (LAI). The largest production of chicory Amazon was obtained in plants grown at a spacing of 0.25 × 0.25 m subjected to pruning floral tassel. The highest yield for Amazon chicory was obtained in plants grown at a spacing of 0.15 × 0.15 m submitted pruning floral tassel.
Production chicory Amazon cultivated under density planting and pruning of floral tassel
Keywords: Condimental vegetable; Eryngium foetidum L.; Protected cultivation; Spacings